Determinantes emocionais do compartilhamento entre consumidores online - Feitosa, Wilian Ramalho (2014)
This study aims to analyze the roles of emotional arousal and valence as influencers of the level of information sharing propensity among online consumers. People share content both talking about and by using an online social network. Sharing leads to greater diffusion of different content, making the same to come viral, reaching many audiences (Ho; Dempsey, 2010). Studies have identified that positive, useful or exciting content go viral more likely than others do (Berger; Milkman 2012). Moreover, some people used to share more than others did. Some authors call them brand advocates. To examine this, four experiments were performed: the first compared the propensity to share news in different valences and arousal levels (2x2); the second compared the propensity to share among news and advertisements with different valences (2x2); the third compared how self-declared brand advocates respond to content of different valences; and The fourth compared the propensity to share advertisements with different marketing stimuli to share (none, tip from a friend or participation in a contest) and positive and negative (3x2) valences. The main findings were: a) The more positive and emotionally charged online content were, the more propensity to share they have had; however, b) negative content were considered more useful and more emotionally charged. Moreover, c) if the content were about a brand which the consumer is an advocate, he/she will write longer answers than other people; and d) if the content were recomended for a friend, the odds to consumer be engaged will increase. The main contribution is to assist in theoretical and managerial understanding about the impact of valence, arousal, utility and brand advocacy on virality, enabling organizations to scale their communication efforts and select the best approaches to their messages